Amelioration of Metabolic Syndrome by Co-Administration of Lactobacillus johnsonii CRL1231 and Wheat Bran in Mice via Gut Microbiota and Metabolites Modulation - Matias Russo; Antonela Marquez; Estefanía Andrada; Sebastián Torres; Arlette Santacruz; Roxana Medina; Paola Gauffin-Cano (Metabolites)
Background/Objectives: Lactobacillus johnsonii CRL1231 (Lj CRL1231) is a strain with feruloyl esterase (FE) activity that enhances ferulic acid (FA) release from wheat bran (WB) and has potential as a probiotic for metabolic syndrome (MS). Given the potential health benefits of FA and its microbial metabolites, this study aimed to evaluate the therapeutic effect of Lj CRL1231 co-administered with WB in a mouse model of metabolic syndrome (MS) induced by a high-fat diet (HFD). Methods: Mice were divided into three groups and fed for 14 weeks as follows: the Control group (standard diet), the MS group (HFD+WB), and the MS+Lj group (HFD+WB and Lj CRL1231-dose 108 cells/day). Specifically, we analyzed the changes in the intestinal microbiota (IM), colonic FE activity, generation of FA-derived and fermentation metabolites, and metabolic and inflammatory parameters. Results: Improvements in the MS+Lj group compared to the MS group included the following: a—a 38% increase in colonic FE activity, leading to elevated levels of FA-derived metabolites (e.g., dihydroferulic, dihydroxyphenylpropionic, and hydroxyphenylpropionic acids); b—a significant shift in the IM composition, with a 3.4-fold decrease in Firmicutes and a 2.9-fold increase in Bacteroidetes; c—a decrease in harmful bacteria (Desulfovibrio) by 93%, and beneficial bacteria like Bifidobacterium increased significantly (6.58 log cells/g); d—a 33% increase in total SCFAs; e—a 26% reduction in the adiposity index; f—a 12% increase in HDL cholesterol and a 19% reduction in triglycerides; g—normalized glucose and insulin resulting in a 2-fold lower HOMA-IR index; h—an improved inflammatory profile by decreasing TNF-α, IFN-γ, and IL-6 (3-, 5-, and 2-fold, respectively) and increasing IL-10 by 2-fold; i—alleviation of liver damage by normalizing of transaminases AST (19.70 ± 2.97 U/L) and ALT (13.12 ± 0.88 U/L); j—evidence of reduced oxidative damage. Conclusions: The co-administration of L. johnsonii CRL1231 and WB exerts a synergistic effect in mitigating the features of MS in HFD-fed mice. This effect is mediated by modulation of the gut microbiota, increased release of bioactive FA-derived compounds, and restoration of metabolic and inflammatory homeostasis. This strategy represents a promising dietary approach for MS management through targeted microbiota–metabolite interactions.